PENGARUH KUALITAS LAYANAN, CITRA MEREK, PERSEPSI HARGA, DAN KELOMPOK REFERENSI TERHADAP LOYALITAS PELANGGAN - Reykhan, Muhammad; Moko, Wahdiyat (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
Many competitors with the same segment as Kopi Kenangan emerged as competitors such as Excelso and Starbucks. Customer loyalty is needed so that Kopi Kenangan remains superior and survives in the market. The purpose of this study is to identify the effects of service quality, brand image, price perception, and reference group on the loyalty of Kopi Kenangan customers in Malang city. The type of research conducted in this research is explanatory research. The sampling technique used was non-probability sampling with purposive sampling and survey methods. The data of this quantitative research was obtained from online questionnaires distributed to 95 respondents. The results of the multiple linear regression analysis have led to a finding that service quality, brand image, price perception, and reference group have positive and significant effects on the loyalty of Kopi Kenangan customers in Malang city. The results of this study can be used as a reference in increasing customer loyalty, especially in the coffee business in Malang city.